Analisis Yuridis Cerai Gugat Karena Kekerasan Dalam Rumah Tangga: (Studi Putusan Nomor 126/Pdt.G/2024/PA.Sda) - Rizkya Fitri Ananda Hariyanto; Wiwin Yulianingsih (CV Rewang Rencang, 2025)
Unresolved domestic problems often lead to divorce lawsuits, including due to domestic violence. This study analyzes Decision Number 126/Pdt.G/2024/PA.Sda which states that divorce lawsuits cannot be accepted even though there are strong indications of domestic violence. This study uses a normative legal method with a statute approach, conceptual approach, and case approach. The results of the study show that the panel of judges was incorrect in interpreting domestic violence only as physical violence, even though psychological violence has been proven to be real. This inappropriate decision creates injustice for victims of domestic violence who should receive legal protection.